The main predictive factors of worse outcome in patients with COVID-19 infection hospitalized in temporary COVID hospital - Jovana Djurdjevic; Nina Tomonjic; Andja Cirkovic; Sretko Lukovic; Luka Pavlovic; Melanija Rasic; Marko Perovic; Ana Banko; Ivica Jeremic (Journal of Infection in Developing Countries)
Introduction: After the Serbian community hospitals had reached their full capacity during the pandemic, new institutions were enrolled into the coronavirus disease 2019 (COVID-19) system as temporary COVID hospitals (TCH). These hospitals usually had no intensive care units (ICU) and no possibility to treat severely ill patients. The aim of this study was to identify risk factors at the time of triage that could help identify patients that will require ICU treatment and cannot be treated in a TCH.